The Twig Wasp of Cork Oak - Its Biology and Control - BAILEY, STANLEY F.; STANGE, LIONEL A. (Journal of Economic Entomology, 1966)
Cork oak (Quercus suber L.), the principal source of commercial cork, was introduced to this country in 1858 from acorns sent from Spain. For Many years no pests were noted. In 191R the twig wasp Plagiotrochus suberi Weld, not described until 1926, was observed injuring the tree in California. It has since become a pest, particularly when the cork oak is planted as an ornamental or shade tree. The larvae feed within a jellylike matrix in the small twigs. The resulting dead twigs on the infested trees pn,- sent an unsightly, brushy appearance. The wasp has 1 generation a year. The agamic females emerge from the twigs via a small round hole in May. They are very weak fliers and remain close to the twigs on which they originated. Oviposition is in the twig growth of the previous year. The eggs hatch in late summer and the larvae develop slowly, pupating the following April. The insect has been found in Switzerland and Portugal (where it probably originated) only in the past few years. The time and manner of introduction into California are not known. In North America the wasp is found only in California. Only moderate control has been obtained with sprays of lindane and carbaryl directed against the adult stage. A European aphid, Myzocallis borneri Stroyan, is now a pest of the cork oak in California. This record is new. Other insect pests of the tree in this country are of very minor importance.
The following values have no corresponding Zotero field: label: California;Plagiotrochus suberi;cork oak;twig wasp (PG)
Keywords: California; Cork oak; Plagiotrochus suberi; twig wasp (PG)

The cork oak tree in California - Metcalf, Woodbridge (Economic Botany, 1947)
Cork oaks have been planted in Cali- fornia since about 1855, and there are some outstandingly fine specimen trees growing from San Diego to Eureka at elevations below 2,700 feet. There are about 5,000 trees more than ten years old in the state. Cork oak acorns produced in Cali- fornia average 70 per pound, have a high germinative capacity which can be main- tained for twelve months or more by moist cold storage at 38° F., and during most years it should be possible to obtain from five to ten tons of cork oak acorns from California trees. During the past six years about 200,- 000 seedling trees of cork oak have been grown and distributed to land owners under the cooperative cork oak project. Where carefully planted, protected from animal damage and given adequate irri- gation, shade and care, many of these plantations have shown excellent sur- vival and growth. Because of the kind interest and co- operation on the part of owners of cork oak trees, it has been possible to carry on experimental stripping of about 500 cork oaks during the past six years. The stripping season has been found to be from about July 1 to early in October. Most vigorous and full-crowned trees can be stripped easily with the special tools developed and with virtually no damage to the inner bark. It is not advisable to strip trees which are thin crowned or suffering from drought, insects or dis- ease. Removal of cork from ornamental cork oaks changes their appearance but does not seriously check their growth or lessen their ornamental character. The 15 tons of cork has been quite thoroughly tested and found to be well suited for the making of composition cork articles, insulation blocks and other been rapid and satisfactory with trees, usually regaining the diameter before stripping in five years. Indications are that the reproduction cork is of excellent quality. Trees 25 to 30 years of age when stripped have put on a growth of 100 pounds of reproduction cork in five years. The most serious insect enemy of the cork oak in California is the gall wasp which kills many twigs, particularly on trees in dry locations. There is no known control for this pest. If the cooperative distribution of trees can be continued until there are one mil- lion cork oaks growing in California, they will when 30 years old contain an emergency supply of 50,000 tons of cork. This amount may be increased and the quality improved by successive stripping of the trees after they become 20 years of age.
Keywords: acorns; California; Cork; cork oak trees; diameter; growth (voyant); stripping